Synthesis of natural urolithin M6, a galloflavin mimetic, as a potential inhibitor of lactate dehydrogenase A. Issue 46 (9th November 2016) - Rupiani, Sebastiano; Guidotti, Laura; Manerba, Marcella; Ianni, Lorenza Di; Giacomini, Elisa; Falchi, Federico; Stefano, Giuseppina Di; Roberti, Marinella; Recanatini, Maurizio
Abstract : An efficient synthetic pathway has been developed to synthesize for the first time UM6, identified as a suitable hit in the search for new LDH-A inhibitors. Abstract : Glycolysis is the main route for energy production in tumors. LDH-A is a key enzyme of this process and its inhibition represents an attractive strategy to hamper cancer cell metabolism. Galloflavin is a reliable LDH-A inhibitor as previously identified by us; however, its poor physicochemical properties and chemical tractability render it unsuitable for further development. Therefore, a rational design was undertaken with the aim to reproduce the pharmacophore of galloflavin on simpler, potentially more soluble and synthetic accessible scaffolds. Following a process of structural simplification, natural urolithin M6 (UM6), which is an ellagitannin metabolite produced by gut microbiota, was identified as a putative galloflavin mimetic. In the present study, the synthesis of UM6 is described for the first time. An efficient synthetic pathway has been developed, which involved five steps from readily accessible starting materials. The key reaction steps, a Suzuki coupling and an intramolecular C–H oxygenation, have been optimized to improve the synthetic feasibility and provide the best conditions in terms of reaction time and yield. Moreover, this route would be suitable to obtain other analogs for SAR studies. Preliminary biological tests revealed that UM6 was able to smoothly reproduce the behavior of galloflavin, confirming that our approach was successful in providing a new and accessible structure in the search for new LDH-A inhibitors.